PELAKSANAAN PERATURAN DAERAH PROVINSI BALI NOMOR 10 TAHUN 2011 TENTANG KAWASAN TANPA ROKOK DALAM RANGKA PERLINDUNGAN TERHADAP PEROKOK PASIF - Wijana, I Komang; Mudana, I Nyoman (Kertha Negara : Journal Ilmu Hukum, 2014)
This research, entitled "Implementation of the Regulation of Bali Province No. 10 Year 2011 about No Smoking Area Protection in the Context of Passive Smokers". The background of the problems in this research that there are many smokers who smoke freely in any place in terms of not only detrimental to the health of smokers themselve , but also harms the people around him as a result of exposure to cigarette smoke. Normatively since 2001 Government of Bali Province has rules about No Smoking Area through the Regulation of Bali Province No. 10 Year 2011. Based on this background, the problems in this research include: the authority of the Government of Bali Province in No Smoking Area arrangements and the implementation of the Regulation of Bali Province No. 10 Year 2011 about No Smoking Area in order to protect against secondhand smoke. This research is an empirical legal research, which emphasizes the effectiveness of the law, which is based on sources of primary legal materials and secondary legal materials. Based on the discussion of this research, its obtained research results that the Government of Bali Province authorities for the organization of Smoking Area, but has not been effective, because they found smokers who smoke cigarettes even though the region has been performed with prosecution.
Keywords: Government, Law Enforcement, Smoking Area, Passive Smokers